SARS-CoV-2 and HIV: impact on pulmonary epithelial cells - Evans, Nicholas; Schneider, Alina C.; Castro-Piedras, Isabel; Oliver, Ava G.; Mabry, Alexandria B.; Garcia, Amanda K.; Velez-Colon, Maria del C.; Nichols, Jacob; Grisham, Matthew B.; Pruitt, Kevin; Suarez-Martinez, Edu B.; Almodovar, Sharilyn (Life, 2022)
The SARS-CoV-2 pandemic provides a natural opportunity for the collision of coronavirus disease-2019 (COVID-19) with chronic infections, which place numerous individuals at high risk of severe COVID-19. Infection with Human Immunodeficiency Virus (HIV), a global epidemic, remains a major public health concern. Whether prior HIV+ status exacerbates COVID-19 warrants investigation. Herein, we characterized the impact of SARS-CoV-2 in human bronchial epithelial cells (HBECs) previously exposed to HIV.